Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/eat.20982
|View full text |Cite
|
Sign up to set email alerts
|

Visual body perception in anorexia nervosa

Abstract: The paradoxical advantage of patients with AN in detail-based body processing may be associated to their tendency to routinely explore body parts as a consequence of their obsessive worries about body appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 55 publications
(79 reference statements)
6
44
0
Order By: Relevance
“…These studies also found that AN participants correctly judge height, body movements (Garner et al, 1976; Slade et al, 1973; Smeets et al, 1997; Urgesi et al, 2012), and objects (Garner et al, 1976; Slade et al, 1973; Smeets et al, 1997; Urgesi et al, 2012). These findings suggest a specific disturbance of own body image.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…These studies also found that AN participants correctly judge height, body movements (Garner et al, 1976; Slade et al, 1973; Smeets et al, 1997; Urgesi et al, 2012), and objects (Garner et al, 1976; Slade et al, 1973; Smeets et al, 1997; Urgesi et al, 2012). These findings suggest a specific disturbance of own body image.…”
Section: Resultsmentioning
confidence: 83%
“…Studies in AN in adults and adolescents have found abnormalities in attention, and overestimation of body size, specific to images of their own bodies (Garner, Garfinkel, Stancer, & Moldofsky, 1976; Slade et al, 1973; Smeets, Smit, Panhuysen, & Ingleby, 1997; Urgesi et al, 2012). An eye tracking study showed that AN participants focus visual attention on body parts they are dissatisfied with, whereas controls tend to scan the whole body image (Freeman, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, most patients with major-depression (MD; [33]) do not perceive strange-face illusions, since they perceive their immobile faces without emotions, as death statues in the mirror [34]. Further research may be done in patients with body-dysmorphic-disorder (BDD; [57]) and anorexia nervosa (AN; [58]), who suffer from their bodily imaginary appearance that, in terms of their actual physical body, is strongly dissociated. Notwithstanding the important psychopathology of BDD and AN patients, relevant differences in perceptual processes with respect to healthy individuals have not been found in previous studies.…”
Section: Strange-face Illusions and Archetypal Imagerymentioning
confidence: 99%